Mitochondrial dysfunction in gliomas - Katsetos, Christos D; Anni, Helen; Dráber, Pavel (Seminars in pediatric neurology, 2013)
Mitochondrial (mt) dysfunction in gliomas has been linked to abnormalities of mt energy metabolism, marked by a metabolic shift from oxidative phosphorylation to glycolysis ("Warburg effect"), disturbances in mt membrane potential regulation and apoptotic signaling, as well as to somatic mutations involving the Krebs cycle enzyme isocitrate dehydrogenase. Evolving biological concepts with potential therapeutic implications include interaction between microtubule proteins and mitochondria (mt) in the control of closure of voltage-dependent anion channels and in the regulation of mt dynamics and the mt-endoplasmic reticulum network. The cytoskeletal protein βIII-tubulin, which is overexpressed in malignant gliomas, has emerged as a prosurvival factor associated in part with mt and also as a marker of chemoresistance. Mt-targeted therapeutic strategies that are discussed include the following: (1) metabolic modulation with emphasis on dichloroacetate, a pyruvate dehydrogenase kinase inhibitor; (2) tumor cell death via apoptosis induced by tricyclic antidepressants, microtubule-modulating drugs, and small molecules or compounds capable of inflicting reactive oxygen species-dependent tumor cell death; and (3) pretreatment mt priming and mt-targeted prodrug cancer therapy.
Keywords: Molecular Targeted Therapy; mikrotubuly; Mitochondria; Microtubules; cílená molekulární terapie; mutace; Mitochondrial Diseases; Mutation; Humans; mitochondrie; Endoplasmic Reticulum; Glioma; endoplazmatické retikulum; gliom; lidé; mitochondriální nemoci